Glomerular injury induced by vinyl carbamate in A/J inbred mice: a novel model of membranoproliferative glomerulonephritis - Gong, Athena Y.; Qiao, Ying Jin; Chen, Mengxuan; Alam, Zubia; Malhotra, Deepak K.; Dworkin, Lance; Ju, Wenjun; Gunning, William T. (Frontiers in Pharmacology, 2024)
Ethyl carbamate (EC) is a process contaminant found in fermented foods and alcoholic beverages. Metabolic conversion of ethyl carbamate generates vinyl carbamate (VC), a carcinogenic metabolite. EC, as a Group 2A probable human carcinogen, and the more potent VC, are known to cause tumors in rodents. However, their effects on the kidney are unknown and were explored here. Female A/J inbred mice received an intraperitoneal injection of vehicle or VC. Beginning 5 weeks after VC injection, mice showed signs of moribund state. Mouse necropsies revealed renal glomerular injury that histopathologically recapitulated human membranoproliferative glomerulonephritis (MPGN), as evidenced by light microscopy, immunostaining for immunoglobulins and complements, and electron microscopy. To determine the molecular pathomechanisms, a post-hoc analysis was performed on a publicly available RNA-Seq transcriptome of kidneys from control rats and rats treated with fermented wine containing high concentrations of EC. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses of the differentially expressed genes revealed that the complement and coagulation cascades were a top predicted biological process involved. Furthermore, pathway-based data integration and visualization revealed that key regulators of complement activation were altered by high EC treatment. Among these, complement factors (CF) D and H, critical positive and negative regulators of the alternative pathway, respectively, were most affected, with CFD induced by 3.49-fold and CFH repressed by 5.9-fold, underscoring a hyperactive alternative pathway. Consistently, exposure of primary glomerular endothelial cells to EC or VC resulted in induction of CFD and repression of CFH, accompanied by increased fixation of C3 and C5b9. This effect seems to be mediated by Ras, one of the top genes that interact with both EC and VC, as identified by analyzing the chemical-gene/protein interactions database. Indeed, EC or VC-elicited complement activation was associated with activation of Ras signaling, but was abolished by the Ras inhibitor farnesyl thiosalicylic acid.Collectively, our findings suggest that VC, a metabolite of EC, induces glomerular injury in mice akin to human MPGN, possibly via perturbing the expression of complement regulators, resulting in an effect that favors activation of the alternative complement pathway.